Investigating the harms of divorce on the lives of couples and children - Gholami Rad, Zeinab; Veysipour, Fatemeh (Journal of Psychosociological Research in Family and Culture, 2023)
Unfortunately, in the past several years, the downward slope of marriage statistics and on the other hand, the upward slope of divorce was very worrying. The damage caused by divorce is multi-dimensional, that is, couples, families and children are damaged. On the other hand, the most common mental disorder for men after divorce is depression and guilt, while anxiety and material problems and lack of financial security are common injuries for women. Therefore, specialized training in marriage and divorce counseling seems necessary. The harms mentioned in this article are: 1. Fear of loneliness, 2. Guilt, 3. Emotional problems, 4. Identity problem, 5. Role duality, 6. Economic problems, 7. Community evaluation. In addition, in the current research, the difference between men’s and women’s reactions to divorce and the damages that children of divorce are exposed to were investigated.